Nutritional Adequacy Rate (RDA) and Nutritional Value Information (ING) of Tuna Kering Kayu Fish Canned with Tuna Fish Bone Flour Substitution - Tangke, Umar; Katiandagho, Bernhard; Rochmady, Rochmady (Sangia Research Media and Publishing, 2020)
The nutritional adequacy figure, which is then informed in the ING, is a value that shows the average need for certain nutrients that must be met every day for almost all people with certain characteristics including age, gender, level of physical activity, and physiological conditions, to live. healthy. Information on nutritional value aims to inform the nutritional content contained in food or beverages as a guide for consumers to make choices before deciding to buy packaged food or beverage, so this research aims to test the Nutritional Adequacy Rate (RDA) of wood dried tuna which is then informed. in the form of Nutritional Value Information (ING) on the packaging label for wood dried tuna products. The laboratory test results showed that the diversified product of wood dried tuna with fish bone meal substitution after being processed with modern packaging through the canning process has a nutritional adequacy rate (RDA) per 50 g is total energy 80 kcal, 2g total fat, 1g saturated fat, cholesterol 13mg, 12g protein, 3g total carbohydrates, 1g dietary fiber, 1g sugar, 150mg sodium, 180mg potassium, 52.44 mg calcium, 1g iron.